Design and Implementation of Internet of Things Based Irrigation System - Okandeji, A. A.; Onaifo, F.; Kabir, M. T.; Yakubu, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This work considered the design and implementation of an Internet of things (IoT) based irrigation system that encourages efficient and optimal use of water management practice. The proposed IoT based irrigation system promotes user acknowledgment practice on farmlands by monitoring the soil moisture value and other environmental parameters. This system, which is based on IoT, stores the sensor data, and the water pump can be monitored via the internet using a ThingSpeak channel. Using a micro-controller which coordinates system activities, a wireless fidelity (WIFI) module which transmits the sensed data to the cloud, a motor driver which controls the pump, a digital temperature and humidity (DHT)11 sensor which monitors environmental parameters, and a YL-69 soil moisture sensor, an IoT based irrigation system is implemented. Results obtained showed that the system irrigates the soil based on the defined threshold value of the soil moisture in order to promote efficient and optimal utilization of water management practice. Additionally, farmers can monitor the irrigation processes remotely from a ThingSpeak channel, which gives a graphical representation of the soil moisture value, pump status, temperature and humidity value as well as the flow rate within the environment.